2007
DOI: 10.1093/ndt/gfm724
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated interferon alfa-2a (40 kD) and ribavirin in haemodialysis patients with chronic hepatitis C

Abstract: In our series of seven patients, we were able to use RBV monitoring drug levels in combination with PEG-IFN alfa-2a (40 kD) and achieve high sustained response rates. However, Epo and transfusion requirements may increase. In two patients adverse events were observed, but manageable with dose reduction of PEG-IFN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 22 publications
2
47
0
1
Order By: Relevance
“…A number of small studies using RBV plasma trough concentrations and/or hemoglobin measurements to guide therapy have shown average RBV doses between 133 and 200 mg daily to be optimal (16,17,22). The current study used RBV doses of 200 mg daily and showed plasma levels approximately 20% lower than those for patients with normal renal function.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A number of small studies using RBV plasma trough concentrations and/or hemoglobin measurements to guide therapy have shown average RBV doses between 133 and 200 mg daily to be optimal (16,17,22). The current study used RBV doses of 200 mg daily and showed plasma levels approximately 20% lower than those for patients with normal renal function.…”
Section: Discussionmentioning
confidence: 69%
“…Current treatment guidelines recommend RBV doses ranging from 200 to 800 mg/day in patients with moderate to severe kidney disease not undergoing hemodialysis and markedly reduced RBV daily doses in patients on dialysis (5). It should be recognized that the recommendations in ESRD are based upon small case series from clinical practice using RBV doses of 200 to 400 mg/day (15)(16)(17). Given that the inclusion of RBV in current and future HCV treatment regimens will be required for the foreseeable future and given the large number of HCV-infected patients with markedly impaired renal function and the limited data on dosing of RBV in this patient population, the current study was undertaken to evaluate the safety, tolerability, and pharmacokinetic (PK) profile of RBV in patients with various degrees of renal impairment who received RBV plus pegylated interferon (IFN) for treatment of HCV infection.…”
mentioning
confidence: 99%
“…Nevertheless, physicians are reluctant to use ribavirin in patients on dialysis given the fear of the drug-related side effects, particularly hemolytic anemia, that can be exacerbated in the presence of ESRD (72). Despite this contraindication in ESRD patients, the available small studies of combined treatment with ribavirin and IFN showed that SVR response was achieved in more than 50% of patients, hemoglobin level was successfully maintained by erythropoietin and iron therapy, and the drop-out rate from anemia was limited (73)(74)(75)(76)(77)(78)(79) (Table 3). Close monitoring for patients with ESRD is mandatory to avoid the risk of ribavirin overdosing.…”
Section: Treatment Of Hcv Infectionmentioning
confidence: 99%
“…Most of the included studies involved IFN monotherapy; but recent studies suggest that combined pegylated IFN and low-dose ribavirin, with careful monitoring of ribavirin plasma levels, may result in higher SVR rates (48). Finally, although SVR rates appear higher in IFN-treated HD patients, SVR is only a surrogate outcome.…”
Section: Discussionmentioning
confidence: 99%